Public opinion, the press, and public policy - Kennamer, J. David (Westport ; London : Praeger, 1994)
This contributors' volume examines the ways in which public opinion affects public policy via the news media. Insofar as the media represent or characterize the public, they represent or frame policy questions and decisions. They convey--accurately or inaccurately--the overall climate of public opinion to policymakers, and are themselves used as evidence of public opinion by policymakers. This work draws together theory and original research concerning the role of the press in shaping public policy and links the fields of journalism, mass communications, and political science. This work will be of interest to scholars and practitioners in journalism, communications studies, public policy, government, and political science.
Ch. 1. Public Opinion, the Press, and Public Policy: An Introduction / J. David Kennamer -- Ch. 2. The Public's Knowledge of Politics / Michaele X. Delli Carpini and Scott Keeter -- Ch. 3. Effective Public Opinion / James B. Lemert -- Ch. 4. Interest Groups in the News / Lucig Danielian -- Ch. 5. r
Includes bibliographical references and index.
Keywords: Public opinion; Public opinion -- United States; Mass media -- Political aspects; Mass media -- Influence; Mass media and public opinion -- United States; United States -- Politics and government